2009
DOI: 10.1007/s10549-009-0484-0
|View full text |Cite
|
Sign up to set email alerts
|

The circadian gene NPAS2 is a novel prognostic biomarker for breast cancer

Abstract: Mounting evidence suggests that neuronal PAS domain protein 2 (NPAS2) and other circadian genes are involved in tumorigenesis and tumor growth, possibly through their control of cancer-related biologic pathways. A missense polymorphism in NPAS2 (Ala394Thr) has been shown to be associated with risk of human tumors including breast cancer. The current study further examined the prognostic significance of NPAS2 in breast cancer by genotyping the Ala394Thr polymorphism and measuring NPAS2 expression. DNA extracted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 27 publications
3
47
1
Order By: Relevance
“…Furthermore, a high level of NPAS2 expression was strongly associated with improved diseasefree survival (HR = 0.43, 95% CI: 0.21-0.86, P trend = 0.022) and overall survival (HR = 0.42, 95% CI: 0.19-0.96, P trend = 0.036) [15]. Thus, it's reasonable to hypothesis that the genetic and expression variations of NPAS2 will be in relation to clinical characteristics of breast cancer and breast cancer survival.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, a high level of NPAS2 expression was strongly associated with improved diseasefree survival (HR = 0.43, 95% CI: 0.21-0.86, P trend = 0.022) and overall survival (HR = 0.42, 95% CI: 0.19-0.96, P trend = 0.036) [15]. Thus, it's reasonable to hypothesis that the genetic and expression variations of NPAS2 will be in relation to clinical characteristics of breast cancer and breast cancer survival.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, the same group also reported that rs2305160 may borderline significantly related to breast cancer survival, where as NPAS2 expression is a significant biomarker for breast cancer survival [15]. As NPAS2 is a trans-activator to control the expression of downstream tumor-related genes, we searched potentially functional SNPs in the promoter region, 5 0 -untranslated region (UTR) and 3 0 UTR, which may influence gene expression, and found a putative functional SNP (rs3739008) located at 3 0 UTR of NPAS2.…”
Section: Introductionmentioning
confidence: 92%
“…Population based studies have identified associations with variants in circadian pathways genes and risk of breast cancer [2–4], prostate cancer [5, 6] and non-Hodgkin’s lymphoma [7, 8]. Variants in these genes have also been associated with survival in hepatocellular carcinoma [9], breast [10], prostate [11] and colon [12] cancer.…”
Section: Introductionmentioning
confidence: 99%
“…This was shown for colorectal cancer, 40,41 chronic lymphocytic leukemia, 42 epithelial ovarian cancer, 43 and breast cancer. 44 In various epidemiological studies, it was shown that single nucleotide polymorphisms in clock genes are associated with higher cancer risk for prostate cancer (CRY2 rs1401417: G.C, 1.7-fold higher risk), 45 breast cancer (NPAS2 Ala394Thr), 46 non-Hodgkin's lymphoma (CRY2 rs11038689, rs7123390, rs1401417), 47 and colorectal carcinoma (CLOCK1 311T.C, CC 2.78-fold and TC 1.78-fold higher risk). 48 Gene expression of all three PERs is deregulated in breast cancer cells, and PER1 expression is downregulated in most patients.…”
Section: Circadian Rhythms and Cancermentioning
confidence: 99%